INCREASING THE COMPETITIVENESS OF INSURERS AND MATCHING THE REQUIREMENTS OF INTERNATIONAL STANDARDS - Mavrulova Nilufar Abdukhalilovna (International Journal of Economic Integration and Regional Competitiveness, 2024)
In this article, it is stated that the operation of insurance companies in accordance with the standards of solvency and maintaining financial stability will increase their competitiveness and investment attractiveness and open the way to international markets. Also, the experience of developed countries regarding the implementation of the Solvency II directive on compliance with solvency standards was studied, relevant conclusions were drawn, and proposals and recommendations were developed in this regard.